2022
DOI: 10.34133/2022/9798679
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Quantum Advantage with Quantum Coupon Collector

Abstract: An increasing number of communication and computational schemes with quantum advantages have recently been proposed, which implies that quantum technology has fertile application prospects. However, demonstrating these schemes experimentally continues to be a central challenge because of the difficulty in preparing high-dimensional states or highly entangled states. In this study, we introduce and analyze a quantum coupon collector protocol by employing coherent states and simple linear optical elements, which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…Still, either of these special forms cannot be reconciled with either of Equations ( 24) and (25). Both Equations ( 38) and (39) confirm once again that the solutions in Equations ( 26) and (27) for the chiral case are specially constructed such that they are not reduceable to any for the achiral case. In this respect, the reductions made in Section 5 for the achiral case from the chiral case should be understood carefully.…”
Section: Well-posed Problems For Electromagnetic Waves Through Chiral...mentioning
confidence: 74%
See 1 more Smart Citation
“…Still, either of these special forms cannot be reconciled with either of Equations ( 24) and (25). Both Equations ( 38) and (39) confirm once again that the solutions in Equations ( 26) and (27) for the chiral case are specially constructed such that they are not reduceable to any for the achiral case. In this respect, the reductions made in Section 5 for the achiral case from the chiral case should be understood carefully.…”
Section: Well-posed Problems For Electromagnetic Waves Through Chiral...mentioning
confidence: 74%
“…With the discussions on Equations ( 36) and (37) at hand, let us revisit Equations ( 26) and (27). We then take an achiral limit 0  → for the chiral case, thereby obtaining ( ) ( )…”
Section: Well-posed Problems For Electromagnetic Waves Through Chiral...mentioning
confidence: 99%
“…Machine learning is perfect for solutions to data-processing problems, such as parameter estimation, data prediction, data sorting and pattern recognition, outlier detection, etc [19], [20]. In the quantum field, recent studies have shown that machine learning exhibits quantum advantages in experiments [21], [22]. In quantum communication, there are some researches involving machine learning to solve the problems in quantum communication [23]- [26].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, rapid progress has been made in the research and development of standalone quantum computers [1], both in terms of software and hardware, to the point where it is debated whether quantum computational supremacy has achieved [2][3][4]. In the near future, standalone quantum computers are expected to show innovative performance in various fields, such as machine learning [5][6][7][8][9] and computational chemistry [10][11][12][13][14]. On the other hand, it is known that much quantum information processing, including various different types of quantum cryptography such as quantum public-key cryptography [15], quantum blind computation [16,17], and quantum money [18,19] cannot be realized on standalone quantum computers but only on quantum networks [20], where a quantum network of a large size is called quantum internet [21,22].…”
Section: Introductionmentioning
confidence: 99%